PENGARUH KOMPENSASI DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA CV. RODA JATI KARANGANYAR PALEMBANG TAHUN 2016 - Marsinah, Marsinah (Jurnal Ecoment Global, 2021)
Employees are a very important resource for the survival of the company, so it is necessary to pay attention to matters relating to employee performance in order to achieve company goals. The purpose of this study was to determine the effect of compensation and work environment factors on employee performance and the most dominant factors in influencing employee performance at CV. Roda Jati Karanganyar. The type of research used is descriptive qualitative and quantitative descriptive. In accordance with the objectives of this study, the sample used is the employees of CV. Roda Jati Karanganyar. Through this preliminary research, it is hoped that in addition to producing a follow-up research formulation, the main thing is to become a reference material for companies to be able to determine human resource development strategies to achieve company goals.Key words: Compensation, Work Environment and Employee Performance